Nutritional evaluation of shiitake mushroom (Lentinula edodes (Berk.) Pegler in function of the strain and type of cultivated eucalyptus - Andrade, Meire Cristina Nogueira de (2008)
The nutritional value of Lentinula edodes (Berk.) Pegler varies according to strain, processing after harvesting, development stage of the basidiomata, and type of substrate used. The objective of this work was to evaluate the nutritional value of L. edodes basidiomata based on strain and type of eucalyptus cultivated. The experimental design was totally randomized in 2 × 10 factorial design (L. edodes strains × eucalyptus type) totalizing 20 treatments with 2 repetitions with each one correspondingto a sample of dehydrated and triturated basidiomata. According to the results obtained, it was verified that the nutritional properties of L. edodes (raw protein, ethereal extract, ashes, and raw fiber) are influenced by the eucalyptus × fungus interaction. Thus, the best results found were: raw protein - LE-96/18 strain cultivated in E. urophylla logs, with the average of 24,3%; ethereal extract - LE-96/18 strain cultivated in logs of clone 23 with the average of 3,0%; ashes -LE-96/18 strain cultivated in E. paniculata and E. camaldulensis logs and LE-95/01 strain cultivated in E. dtriodora logs with averages of 5,0%; raw fiber - LE-95/01 strain cultivated in E. paniculata logs with averages of 20,5%.